The Tenth Grade Vocational Students' Mathematical Communication Patterns based on Personality Types (Universitas Negeri Semarang, 2021)
The differences in individual’s personality create diversity in communication. This study is aimed to describe the students’ written mathematical communication patterns based on personality types. It is a qualitative descriptive study in X grade vocational high school students of SMK N Tengaran, Semarang Regency in 2019/2020. The data were obtained by documenting the results of students’ mathematical communication tests and interviews. The research findings show that there is no unique pattern for each personality type in the mathematical communication patterns associated with sequence of working on questions. However, in mathematical communication patterns that are related to the type of error performed, the Introvert - Neurotic personality type makes the most types of errors in using incorrect variables and calculation errors.